Universal Decolonization Reduces MDRO Burden on High-Touch Objects in Nursing Home Resident Rooms and Common Areas. (October 2020) - Gussin, Gabrielle M.; Singh, Raveena D.; Saavedra, Raheeb; Catuna, Tabitha D.; Heim, Lauren; Mendez, Job; Franco, Ryan; Estevez, Marlene; Custodio, Harold; Evans, Kaye D.; Peterson, Ellena M.; McKinnell, James A.; et al.
Abstract : Background: More than half of nursing home (NH) residents harbor a multidrug-resistant organism (MDRO), and MDRO contamination of the environment is common. Whether NH decolonization of residents reduces MDRO contamination remains unclear. The PROTECT trial was a cluster-randomized trial of decolonization versus routine care in 28 California NHs from April 2017 through December 2018. Decolonization involved chlorhexidine bathing plus nasal iodophor (Monday–Friday, every other week), and it reduced resident nares and skin MDRO colonization by 36%. Methods: We swabbed high-touch objects in resident rooms and common areas for MDROs before and after the 3-month decolonization phase-in (April–July 2017). Five high-touch objects (bedrail, call button and TV remote, doorknob, light switch, and bathroom handles) were swabbed in 3 resident rooms per NH based on care needs (Alzheimer's disease and related dementias (ADRD), ie, total care; ADRD, ambulatory care; and short stay). Five high-touch objects were also swabbed in the common area (nursing station, table, chair, railing, and drinking fountain). Swabs were processed for methicillin-resistant S. aureus (MRSA), vancomycin-resistant Enterococcus (VRE), extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae, and carbapenem-resistant Enterobacteriaceae (CRE). We used generalized linear mixed models to assess the impact of decolonization on MDRO environmental contamination when clustering by NH and room and adjusting for room type and object because unclustered and unadjusted results are likely to be inaccurate. Results: A high proportion of rooms were contaminated with any MDRO in control NHs: 43 of 56 (77%) in the baseline period and 46 of 56 (82%) in the intervention period. In contrast, decolonization NHs had similar baseline contamination (45 of 56, 80%) but lower intervention MDRO contamination (29 of 48, 60%). When evaluating the intervention impact using multivariable models, decolonization was associated with significantly less room contamination for any MDRO (OR, 0.25; 95% CI, 0.06–0.96; P = .04) and MRSA (OR, 0.16; 95% CI, 0.05–0.55; P = .004) but nonsignificant reductions in VRE contamination (OR, 0.86; 95% CI, 0.23–3.13) and ESBL contamination (OR, 0.13; 95% CI, 0.01–1.62). CRE was not modeled due to rare counts (2 rooms total). In addition, room type was important, with common areas associated with 5-fold, 9-fold, and 3-fold higher contamination with any MDRO, MRSA, and VRE, respectively, compared with short-stay rooms. Conclusions: The high burden of MDROs in NHs calls for universal prevention strategies that can protect all residents. Although decolonization was associated with an 84% reduction in odds of MRSA contamination of inanimate room objects, significant reductions in VRE or ESBL contamination were not seen, possibly due to the lower proportion of baseline contamination due to these organisms. Multimodal strategies are needed to address high levels of MDRO contamination in NHs. Funding: None Disclosures: Gabrielle Gussin: Stryker (Sage Products): Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Clorox: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Medline: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Xttrium: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes.